Maize yield as affected by organic inputs and urea in the West African moist savanna - Vanlauwe, Bernard; Aihou, K.; Aman, S.; Iwuafor, E.N.O.; Tossah, B.K.; Diels, J.; Sanginga, Nteranya; Lyasse, O.; Merckx, Roel; Deckers, J. (Wiley, 2001)
Nutrient depletion is a major constraint to crop production for moist savanna soils, and inputs of nutrients are required to overcome this constraint. The impact of sole and combined applications of organic inputs (OIs) [fresh tree prunings, Pueraria phaseoloides (Roxb.) Benth. residues, and manure] and urea [(NH2)2CO] on maize (Zea mays L.) performance was investigated at four sites in West Africa. Interactions between OIs and urea resulting in added benefits from their mixed rather than sole application were quantified, and likely causes were evaluated. Maize in the mixed treatments, receiving 45 kg ha?1 urea N and 45 kg ha?1 N as OIs, produced 1.6 and 3.7 Mg ha?1 grain in Sékou and Glidji, respectively. Based on the yields from sole application of either OIs or urea, added benefits from the mixture were 0.49 Mg ha?1 grain (P < 0.001) in Sékou and 0.58 Mg ha?1 (P < 0.15) in Glidji. These benefits were generated during grain filling, which was characterized by drought, and they were likely caused by improved soil water conditions with mixed applications compared with sole applications. Nitrogen recovery from urea was higher in the combined treatments (44% in Sékou and 32% in Glidji) relative to the sole urea treatments (22% in Sékou and 15% in Glidji). Positive interactions between OIs and urea occurred at two of four sites and were likely caused by improved soil water conditions after applying OIs. Organic inputs can alleviate constraints to crop growth other than N depletion and, as such, improve the use efficiency of N fertilizer.